COVID-19 and learners with disabilities: Towards divergent praxis in teacher preparation for equity and epistemic justice - Adigun, O. T.; Nzima, D. R.; Maphalala, M. C.; Ndwandwe, N. D. (South African Journal of Higher Education, 2022)
Emergence of COVID-19 further exposed educational inequalities and epistemic injustices experienced by learners with disabilities (LwDs). COVID-19 presents additional challenges for teachers and LwDs whose life and active learning engagements depends largely on social interaction. While the lockdown persisted, teachers of LwDs became anxious about potential relapse of previously gained learning outcomes and aggravated disabling condition. Unfortunately, there seem to be less teachers’ capacities to continually foster learning among their LwDs during the lockdown because there exist low teachers’ morale and pedagogical gaps for digital teaching. Based on current realities, it is evident that there is need for a paradigm shift in teacher preparation and training towards equity and epistemic justice for LwDs. Hence, this intellectual piece advanced the need to modify the existing teacher education curriculum to extensively build on teachers’ morale while it consciously infuses technological pedagogies in preparation programmes of teachers of LwDs in Africa.